2017
DOI: 10.17759/exppsy.2017100210
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate complexity during the temporary systems dedifferentiation

Abstract: * Бахчина А.В. Кандидат психологических наук, научный сотрудник, Институт психологии Россий-ской академии наук (ФГБУН ИП РАН); научный сотрудник, Федеральное государственное автоном-ное образовательное учреждение высшего образования «Национальный исследовательский Нижего-родский государственный университет имени Н.И. Лобачевского» (ФГАОУ ВО НИУ ННГУ имени Н.И. Лобачевского). E-mail: nastya@mail.ru ** Александров Ю.И. Доктор психологических наук, профессор, заведующий лабораторией, Институт психологии Российско… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Using alcohol as a factor of controlled experimental influence on the subject of behavior state (selective oppression of actualization of the most differentiated systems), we have demonstrated that moral assessment is carried out mainly intuitively on the basis of actualization of low-differentiated systems, in the very first place alcohol inhibits the processes of rational reasoning, without disturbing the intuitive assessment of actions [49]. In addition, in the situation of moral evaluation, alcohol intake was associated with changes in the dynamics of the heart rate (increase in heart rate and decrease in RR-interval variability), which can be considered a physiological indicator of systemic dedifferentiation -a reversible decrease in the contribution of the activity of highly differentiated systems to behavior [50,51].…”
Section: The Subject Of Behavior and Moral Assessment Of Actionsmentioning
confidence: 99%
“…Using alcohol as a factor of controlled experimental influence on the subject of behavior state (selective oppression of actualization of the most differentiated systems), we have demonstrated that moral assessment is carried out mainly intuitively on the basis of actualization of low-differentiated systems, in the very first place alcohol inhibits the processes of rational reasoning, without disturbing the intuitive assessment of actions [49]. In addition, in the situation of moral evaluation, alcohol intake was associated with changes in the dynamics of the heart rate (increase in heart rate and decrease in RR-interval variability), which can be considered a physiological indicator of systemic dedifferentiation -a reversible decrease in the contribution of the activity of highly differentiated systems to behavior [50,51].…”
Section: The Subject Of Behavior and Moral Assessment Of Actionsmentioning
confidence: 99%